Tinjauan Hukum Islam terhadap Relasi Agama dan Negara dalam Perspektif al-Ghazali - Jamaludin Jamaludin (Mutawasith: Jurnal Hukum Islam, 2020)
This research aims to analyze the relationship between religion and country in the perspective of Islamic law. Among the scholars who are referenced in religious and state relations is al-Ghazali. His thoughts on the concept of religion and country are interesting to research. This research uses descriptive-qualitative methods in the form of library research. The results showed that between religion and state has a connection, so al-Ghazali analogizes religion and the king as 'two twins', of which religion is a foundation, while the king is the guardian. Something without a foundation will easily collapse and a foundation without guards will disappear. The existence of the king is a necessity for the order of the world, the order of the world is a necessity for religious order, and religious order is a necessity for the attainment of the welfare of the hereafter. Unequivocally, al-Ghazali said that a country that ignores morals (morals, ethics) will gradually suffer destruction or destruction. To that, al-Ghazali offers five ideal and moral conceptions of the state. The five conceptions are interdependence towards happiness, the fusion of science with religion and morals, moral-politics, the head of state who is sincere, and moral in international relations and deeds.